Short-term effects of Y-27632, a rho-associated protein kinase inhibitor, on chromatin supraorganization and DNA amount in epithelial cells of the rat cornea and limbus - Aldrovani, Marcela [UNESP]; Sobrinho, Alexandre A. F. Barros [UNESP]; Mairos, Fernanda Santos [UNESP]; Laus, José Luiz [UNESP] (Wolters Kluwer, 2017)
Purpose: To assess the short-term effects of instilling Y-27632, an inhibitor of Rho/Rho-associated protein kinases, on the chromatin supraorganization and DNA amount of corneal and limbal epithelial cells of healthy rats. Methods: Longitudinal sections (7 mm) of enucleated eyes of healthy rats that received, by instillation, balanced salt solution with or without 10 mM of Y-27632 daily for 7 or 15 days, were subjected to the Feulgen reaction. Feulgen-stained nuclei of corneal and limbal epithelial cells were studied by microscopy and video image analysis to establish the nuclear size (area and perimeter), supraorganization of chromatin (texture and degrees of condensation), and the FeulgenDNA amount. Results: Instillation of Y-27632 for up to 15 days did not change the size of the nucleus or the chromatin texture of corneal and limbal epithelial cells. Samples treated with Y-27632 for 7 days showed condensed chromatin and a high Feulgen-DNA amount. Both corneal and limbal epithelium showed the presence of neartetraploid nuclei corresponding to cells in the S and G2 phases of the cell cycle. The degrees of condensation and Feulgen-DNA amount of the nuclei of epithelial cells of the cornea and limbus of eyes from rats receiving Y-27632 for 15 days did not differ from control (no drug). Conclusions: Changes in chromatin supraorganization and DNA amount, such as seen in this study, are indicative of cell proliferation and do not seem to be associated with disturbances in gene activity and transcription of DNA.
Keywords: Cell proliferation; GTPases; Nucleus; Ocular surface; Rho kinase